MENINGKATKAN KREATIVITAS ANAK MELALUI KEGIATAN FINGER PAINTING DENGAN MEDIA TOTEBAG DI POS PAUD MAHA SURABAYA - widianti, henny; Rofiyarti, fitri (Universitas Narotama, 2024)
This study aims to increase children's creativity through finger painting activities using tote bag media at Maha PAUD Surabaya. Finger painting activities aim to explore and develop imagination and expression through moving the fingers through painting/drawing, color recognition and cultivating a sense of beauty, furthermore through training body muscle movements. This study used Classroom Action Research (PTK), which is based on the Kemmis and Mc Taggart theoretical models. The subjects of this study consisted of 22 students of class B at Maha Paud, Surabaya. The data collection techniques that used in this study was observation and documentation. Researcher used a quantitative approach method to analyze the data. The criterion for the success of this research is if the creative ability is in the BSB criteria (Very Well Developed), or with a value range of 76 – 100%. The result showed that children's creativity increased after the action was carried out through finger painting activities, which provided opportunities for them to make their own project with their own willingness. This enhancement can be seen from the data on the average percentage value in Pre-action indicated that the percentage of children's creativity is 28,79 %. In Cycle I, the percentage of children's creativity increased to 42,42 %. And in Cycle II the percentage of children's creativity increased to 81,81 %. It can be said that this research was successful because the percentage has reached the specified number.